Market competition and bank performance - empirical evidence from the European Union banking sector - Ferreira , Candida (International Journal of Economics and Financial Modelling, 2025)
The main aim of this paper is to empirically test the contribution of market competition to bank performance and the influence of the crises that affected the EU banking sector over the years 2006-2021. Using data sourced from the Moody’s Analytics BankFocus database, the paper presents the results obtained with panel fixed, random, and dynamic GMM estimations. Bank performance is proxied with two variables: bank profitability and bank capitalization. Bank profitability is measured with the return on equity ratio, and bank capitalization is represented with the equity to total assets ratio. Bank competition is measured with Boone indicators and Herfindahl-Hirschman Indices. These two competition measures are separately computed for banks’ profits, loans, and deposits. The findings suggest that competition, evaluated from an efficiency perspective, plays a more crucial role than market concentration in the banking sector in explaining bank performance. Furthermore, the profitability of banks does not appear to be directly linked to their traditional activities. The paper highlights the significant role of political and regulatory authorities in ensuring that legislation and conditions are in place to maintain bank market competition without exacerbating crisis risks while also fostering economic growth.